2020
DOI: 10.1016/j.celrep.2020.107794
|View full text |Cite
|
Sign up to set email alerts
|

The Kinase Activity of Drosophila BubR1 Is Required for Insulin Signaling-Dependent Stem Cell Maintenance

Abstract: Highlights d BubR1 kinase activity is dispensable for the timing and progression of mitosis d BubR1 kinase-dead mutants have attenuated insulin signaling d Loss of BubR1 kinase activity compromises the homeostasis of tissue stem cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…This is perhaps due to the essentiality of mitotic genes for the life of a cell, especially when being cultured in a petri dish. Nonetheless, mitotic genes are often expressed in postmitotic tissues, and several recent studies in model organisms including mice and Drosophila have revealed unexpected roles of mitotic regulators in endocytosis [87][88][89].…”
Section: Functional Engagement Of Mitotic Regulators In Endocytosismentioning
confidence: 99%
See 3 more Smart Citations
“…This is perhaps due to the essentiality of mitotic genes for the life of a cell, especially when being cultured in a petri dish. Nonetheless, mitotic genes are often expressed in postmitotic tissues, and several recent studies in model organisms including mice and Drosophila have revealed unexpected roles of mitotic regulators in endocytosis [87][88][89].…”
Section: Functional Engagement Of Mitotic Regulators In Endocytosismentioning
confidence: 99%
“…Studies in Drosophila have further consolidated this model and suggest it might be an evolutionarily conserved mechanism (Fig. 5B) [89]. The kinase domain of Drosophila BubR1 is able to interact with Drosophila AP2B, and a MIM‐like motif can also be identified on the cytoplasmic tail of Drosophila InR, although this cytoplasmic tail is not very conserved at sequence level between Drosophila and mice.…”
Section: Functional Engagement Of Mitotic Regulators In Endocytosismentioning
confidence: 99%
See 2 more Smart Citations
“…Insulin promotes clathrin-mediated IR endocytosis, which controls the intensity and duration of insulin signaling (50,(56)(57)(58). We and others have previously shown that mitotic regulators and SHP2 (SH2-containing protein tyrosine phosphatase 2)-MAPK (mitogen-activated protein kinase) pathway promote insulin-induced IR endocytosis (59)(60)(61). To study the contributions of the disulfide-linked αCTs to IR endocytosis, we generated HeLa cells stably expressing IR-GFP-WT, -3CS, or -D686-690, and examined the subcellular localization of these IR-GFP proteins (Fig.…”
Section: The Disulfide-linked αCts Are Required For Optimal Ir Signal...mentioning
confidence: 99%